1974
DOI: 10.1002/bjs.1800611106
|View full text |Cite
|
Sign up to set email alerts
|

Gastrin response to food in duodenal ulcer patients before and after selective or highly selective vagotomy

Abstract: The role of the vagus in the gastrin response to a steak meal was investigated in patients with duodenal ulcer. Thirty patients were studied before and after vagal denervationoftheentire stomach (selective vagotomy and pyloroplasty). Basal and stimulated gastrin concentrations in serum, as determined by radio-immunoassay, were higher postoperatively (87 pre-/I I1 postopera- tively (basal) and 2431341 (peak) pglml). Thirty other patients were studied before and afier denervation of the gastric body (highly sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
1

Year Published

1976
1976
1989
1989

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 9 publications
2
16
0
1
Order By: Relevance
“…First, studies using insulin hypoglycemia as a vagal stimulant must be interpreted with caution because there is evidence that hypoglycemic gastrin release is nonvagal (8)(9)(10). For example, the gastrin response to hypoglycemia persists after a complete vagotomy (8,9). Second, meal studies that have been done with atropine (2-4) are not definitive because atropine reduces acid secretion, and the resulting higher antral pH would facilitate gastrin release in response to any stimulant.…”
Section: Introductionmentioning
confidence: 99%
“…First, studies using insulin hypoglycemia as a vagal stimulant must be interpreted with caution because there is evidence that hypoglycemic gastrin release is nonvagal (8)(9)(10). For example, the gastrin response to hypoglycemia persists after a complete vagotomy (8,9). Second, meal studies that have been done with atropine (2-4) are not definitive because atropine reduces acid secretion, and the resulting higher antral pH would facilitate gastrin release in response to any stimulant.…”
Section: Introductionmentioning
confidence: 99%
“…Stadil and Rehfeld [42] found that the stability of the response did not seem to be influenced by postoperative observation time: patterns of response were similar 2 and 14 weeks postoperatively, and no tendency towards change with time was observed. Figure 3 shows gastrin profiles [38].…”
Section: Resultsmentioning
confidence: 99%
“…Our radioimmunoassay, carried out according to the method described by Stadil and R ehfeld [34], showed an interassay variance of 25°/o and in a intraassay variance of 20% [26,31,32,34,36]. Samples of peripheral venous blood were drawn from an indwelling venous catheter at 15-min intervals throughout the examination.…”
Section: Radioimmunoassay Of Gastrinmentioning
confidence: 99%
“…Enhanced gastrin responses to a test meal were observed only in about half the diabetic patients with vagal neuropathy and in the other patients, the same degree of response as seen in normal subjects and diabetic patients without vagal neuropathy. In patients with peptic ulcer, hypergastrinaemia is often detected not only after truncal vagotomy but also after selective proximal vagotomy [14][15][16]. The vagal inhibitory pathway for gastrin release may be located in the proximal stomach [14].…”
Section: Discussionmentioning
confidence: 99%